Same-Sex Marriages inside the Closet: Deconstruction of Subjects of Gay and Lesbian Discourses in Russia - Alexander Kondakov (Oñati Socio-Legal Series, 2011)
This work aims to analyse LGBT discourse in Russia conducted by human rights non-governmental organisations concerned with the protection of gay and lesbian rights in the country. The main emphasis is given to deconstruction of subjectivities of the discourse with tools of Foucaultian and critical discourse-analyses. One of the most evident examples is provided in the last section of the work. It is concerned with strategies employed by the organisations under research to guarantee marriage opportunities to homosexuals in Russia. It was also important for the purposes of the research to uncover the meanings of discursive practices employed by the officials in their discussion of gay and lesbian issues. In this regard, a brief analysis of relevant legal norms and public policies is included in the work. The attitude of state power towards LGBT problems is described in the terms of environment where the human rights organisations have to perform their activities. The role of state power turns out to be important in organising and correcting the strategies of the organisations so long as the strategies are influenced by governmentality of the discourses. It results into a situation where the non-governmental organisations are to some extent governed through workings of political discourses where the power of the authorities sets the scene.